Intersecting epidemics: COVID-19 and HIV in sub-Saharan Africa. A systematic review (2020-2022) - Talent Tapera; Clifford Odimegwu; Rebaone Petlele; Matshidiso V. Sello; Armstrong Dzomba; Oluwatoyin Aladejebi; Million Phiri (AOSIS, 2023)
There has been significant progress with regards to winning the fight against HIV globally, particularly due to the introduction of antiretroviral therapy (ART). COVID‑19 threatened to derail gains in the fight against HIV. As we have started to see with studies on COVID‑19 and HIV, there is a need to 'provide an in‑depth view' in understanding the dynamics between the two epidemics, especially in sub‑Saharan Africa. We, therefore, undertook a systemic review of existing literature to synthesize the effects of COVID‑19 on the utilization of HIV services in sub‑Saharan Africa, the literature on the risks associated with HIV during the COVID‑19 pandemic, and lastly, the innovations and strategies adopted to continue receiving treatment in sub‑Saharan Africa. We conducted a systematic review of studies published between 2020 and April 2022. We searched for relevant sub‑Saharan studies in the following databases: PubMed, Google Scholar, J‑STOR, and Science Direct. The review followed the Preferred Reporting Items for Systematic Reviews and Meta‑Analyses (PRISMA) guidelines. The search identified 647 papers, and after screening, 41 were in line with the inclusion criteria and were included in the review. There was evidence of the negative effects of COVID‑19 on reducing HIV testing, ART treatment, and HIV prevention services. There is evidence pointing to the need for people living with HIV to be prioritized for COVID‑19 vaccinations. Innovations and strategies implemented to mitigate the effects of COVID‑19 on HIV services include community‑based ART distribution, multi‑month ART dispensing, the use of digital technologies, and the use of the already existing HIV infrastructure to fight COVID‑19. It is still imperative that future studies explore the predictors of utilization of HIV services in the advent of COVID‑19.